Happiness orientation & life satisfaction of emerging adults - Rarick, Timothy Michael (Kansas State University, 2008)
Research has determined three main pathways or orientations to happiness: Meaning, Pleasure, and Engagement (Peterson, Park, & Seligman, 2005). Each has shown to have a substantial impact on an individual's satisfaction with life. These orientations to happiness and their impact on life satisfaction were investigated among 342 emerging adults between the ages of 18-25 attending college. Linear multiple regression was conducted to assess the relationship between Life satisfaction and the three orientations of happiness after identifying the variance explained by demographics factors and personality traits. Results indicated first that each orientation to happiness was empirically distinguishable and related among the emerging adult population. Secondly, both Meaning and Pleasure were significant predictors of Life Satisfaction beyond the variance explained by personality; however, Engagement was not. Congruent with previous personality studies (Lykken & Tellegen, 1996; Lynn & Steel, 2006), life satisfaction was positively correlated with extraversion and negatively correlated with neuroticism. These findings indicate a need to understand how happiness and life satisfaction are filtered through a cultural, developmental, and academic lens. Further studies are necessary to determine the attitudes and behaviors in other countries, other life stages, and emerging adults not attending college.
Keywords: Happiness; Life Satisfaction; Emerging Adults; College Students; Health Sciences, Human Development (0758); Psychology, Developmental (0620)